A new automated and putatively versatile synthesis of the PSMA-ligand derivative [18F]DCFPyL using the FASTlabTM synthesizer - Raphaël Hoareau; Tore Bach-Gansmo; Paul Cumming; Dag Erlend Olberg (SpringerOpen, 2022)
Abstract Background Noninvasive molecular imaging using peptides and biomolecules labelled with positron emitters has become important for detection of cancer and other diseases with PET (positron emission tomography). The positron emitting radionuclide fluorine-18 is widely available in high yield from cyclotrons and has favorable decay (t1/2 109.7 min) and imaging properties. 18F-Labelling of biomolecules and peptides for use as radiotracers is customarily achieved in a two-step approach, which can be challenging to automate. 6-[18F]Fluoronicotinic acid 2,3,5,6-tetrafluorophenyl ester ([18F]F-Py-TFP) is a versatile 18F-prosthetic group for this purpose, which can be rapidly be produced in an one-step approach on solid support. This work details an automated procedure on the cassette-based GE FASTlab™ platform for the labeling of a peptidomimetic, exemplified by the case of using the Glu-CO-Lys motif to produce [18F]DCFPyL, a ligand targeting the prostate specific membrane antigen (PSMA). Results From fluorine-18 delivery a fully automated two-step radiosynthesis of [18F]DCFPyL was completed in 56 min with an overall end of synthesis yield as high as 37% using solid phase extraction (SPE) purification on the GE FASTlab™ platform. Conclusions Putatively, this radiolabeling methodology is inherently amenable to automation with a diverse set of synthesis modules, and it should generalize for production of a broad spectrum of biomolecule-based radiotracers for use in PET imaging.